2012
DOI: 10.1186/1471-230x-12-128
|View full text |Cite
|
Sign up to set email alerts
|

Role of tight junction proteins in gastroesophageal reflux disease

Abstract: Background: Gastroesophageal reflux disease (GERD) is associated with impaired epithelial barrier function that is regulated by cell-cell contacts. The aim of the study was to investigate the expression pattern of selected components involved in the formation of tight junctions in relation to GERD. Methods: Eighty-four patients with GERD-related symptoms with endoscopic signs (erosive: n = 47) or without them (non-erosive: n = 37) as well as 26 patients lacking GERD-specific symptoms as controls were included.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
3
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 63 publications
0
33
3
3
Order By: Relevance
“…Although no change in occludin or ZO-1 expression has been reported in GERD patients, the expression of CLDN1 and CLDN2 mRNA and protein has been reported to be increased [34] and unchanged [35] in GERD, and the expression of CLDN1 and CLDN4 has been reported to be decreased in GERD [33]. The reason for these inconsistent results may be due to the fact that total CLDN protein was measured rather than a specific subpopulation of CLDNs.…”
Section: Involvement Of Tj Proteins In Diseases Gastroesophageal Reflcontrasting
confidence: 38%
“…Although no change in occludin or ZO-1 expression has been reported in GERD patients, the expression of CLDN1 and CLDN2 mRNA and protein has been reported to be increased [34] and unchanged [35] in GERD, and the expression of CLDN1 and CLDN4 has been reported to be decreased in GERD [33]. The reason for these inconsistent results may be due to the fact that total CLDN protein was measured rather than a specific subpopulation of CLDNs.…”
Section: Involvement Of Tj Proteins In Diseases Gastroesophageal Reflcontrasting
confidence: 38%
“…Thirdly, there are many molecules associated with the integrity of esophageal and laryngeal epithelium in addition to claudin-3. Mö nkemü ller et al [22] reported the missing correlation between the expression of tight junction-related components [occludin, claudin-1, -2, zona occludens (ZO-1, -2)] and DIS of the esophageal epithelium in GERD patients. Further research is needed to evaluate the role of claudin-3 and other molecular markers in GERD and LPR.…”
Section: Discussionmentioning
confidence: 99%
“…Animal and in vitro models of GERD have shown changes in expression and localization of Claudin-3 and -4 10, 11 . In human studies, expression of Claudin-1, -2 and -4, ZO-1, filaggrin and occludin are reportedly altered in GERD, but no correlation has been found with histopathological parameters such as DIS and basal cell hyperplasia 1214 . NERD patients exhibit no change in the expression of these proteins 12 .…”
Section: Histopathologic Biomarkersmentioning
confidence: 97%
“…In human studies, expression of Claudin-1, -2 and -4, ZO-1, filaggrin and occludin are reportedly altered in GERD, but no correlation has been found with histopathological parameters such as DIS and basal cell hyperplasia 1214 . NERD patients exhibit no change in the expression of these proteins 12 . Furthermore, direct correlation between acid exposure and pathology is lacking.…”
Section: Histopathologic Biomarkersmentioning
confidence: 97%